ANALISIS KINERJA PROTOKOL ROUTING DINAMIS IS-IS UNTUK MENINGKATKAN PERFORMANSI JARINGAN HYBRID KAMPUS UNUD DENPASAR - Binti Dona, Sufiana; Wiharta, Dewa Made; Indra ER, Ngurah (Jurnal SPEKTRUM, 2023)
As a center for Information and Communication Technology services, the Global Distance Learning Network (GDLN) of Udayana University must reconsider the implementation of static routing protocols that have been applied to meet the increasing demands of computer networks. Dynamic routing protocols, such as Intermediate System to Intermediate System (IS-IS), can be used to address the challenges currently faced with static routing, and serve as a more viable option for larger network requirements. This research evaluates the implementation of static routing protocols and IS-IS at the UNUD Denpasar campus using Graphical Network Simulator-3 to assess the future utilization of the IS-IS routing protocol. Quality of Service (QoS) parameters are used to assess network performance, while the scenarios include PING intervals with settings close to streaming YouTube videos. The research findings reveal that both routing protocols exhibit good service quality, meeting TIPHON criteria with excellent evaluations for packet loss, throughput, and delay, in addition to satisfactory criteria for jitter. Simulation tests demonstrate the superiority of the IS-IS routing protocol compared to static routing when transmitting data in high-resolution streaming video formats like 480p, 720p, and 1080p. On the other hand, static routing is more suitable for disseminating data consisting of lower-resolution streaming videos (360p). Based on the research results, it can be inferred that the dynamic routing protocol IS-IS is more suitable for meeting network demands on a larger scale.